Opening the black box: structural factor models with large cross-sections - Mario Forni; Domenico Giannone; Marco Lippi; Lucrezia Reichlin (European Central Bank (ECB), 2007)
This paper shows how large-dimensional dynamic factor models are suitable for structural analysis. We establish sufficient conditions for identification of the structural shocks and the associated impulse response functions. In particular, we argue that, if the data follow an approximate factor structure, the “problem of fundamentalness”, which is intractable in structural VARs, can be solved provided that the impulse responses are sufficiently heterogeneous. Finally, we propose a consistent method (and n, T rates of convergence) to estimate the impulse-response functions, as well as a bootstrapping procedure for statistical inference.
Keywords: E0; C1; 330; Dynamic Factor Models; fundamentalness; Identification; structural VARs; VAR-Modell; Makroökonomik; Theorie; Nichtlineare Dynamik